Deciphering the Factors Influencing Labour Underutilization Between Women and Men in West Java, Indonesia - Tjitrajaya, Yohanes Andika Tjitrajaya; Sihombing, Riris Sira Torsina Sihombing; Nadia Restu Utami (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2024)
Exploring unequal employment opportunities, remains a compelling subject, especially in developing countries like Indonesia. West Java as a province in Indonesia exhibits a higher rate of labour underutilization, particularly in the categories of unemployment and underemployment. While numerous studies have focused on highlighting the consequences of labour underutilization on country's development outcomes and individual well-being, this study aims to investigate the determinants of employment outcomes, considering both supply and demand sides at the individual level. Utilizing data from the Indonesian Labour Force Survey (Sakernas) in August 2022, this study used separate multinomial logistic models for women and men. In general, the result indicates that gender bias still pronounced in the West Java’s labour market attachments. This study puts forth actionable policy recommendations such as educational campaigns to challenge entrenched gender norms, targeted skills development programs tailored to women, and improved access to childcare services to facilitate maternal workforce participation.